Pematahan Dormansi Benih Kelapa Sawit (Elaeis guineensisJacq.) dengan Perendaman dalam Air Panas dan Variasi Konsentrasi Ethephon - Belladina Farhana; Satriyas Ilyas; Lalu Firman Budiman (Departemen Agronomi dan Hortikultura, 2013)
This research was held from April to July 2012, located in the seed processing unit of PT Astra Agro Lestari Tbk, Central Borneo. The study consisted of three experiments, the first experiment to determine the effect of water temperature and immersion intensity of seed germination. The first experiment used completely randomized design (CRD) factorial with two factors, water temperature: 27, 60, 70, 80, 90oC and immersion intensity: 1x24, 2x24, 3x24 hours. The second experiment used a single factor of CRD namely ethephon concentration: 0, 0.4, 0.8, 1.2, 1.6%. The third experiment was a continuation from the second experiment with the adding heat drying treatment during a week. The result showed that 3x24 hours soaking treatment in 80oC hot water increased the germination, soaking in ethephon 0.4% inhibited radicle growth resulted abnormal seedlings. Soaking seed in 80oC hot water for 3x24 hours and followed by ethephon and then heat drying treatment for a week increased germination (52.0% maximum growth potential) but still ineffective to break seed dormancy.Key Words: breaking dormancy, ethephon, hot water treatment, oil palm seeds